2017
DOI: 10.5530/ogh.2017.6.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Primary Plasmacytoma of Thyroid Gland—an Interesting Case Diagnosed By FNAC

Abstract: Introduction: Primary plasmacytoma of the thyroid gland is a rare disease. Extramedullary plasmacytoma (EMP) comprises 3-5% of all plasma cell neoplasm. Case report: A 57-yearsold female presented with a large thyroid swelling involving the left lobe and isthmus, firm in consistency and moved a little with deglutition. CT scan revealed a large solid tumor (9.5 cm in greatest dimension) affecting thyroid gland. CT scan report gave differential diagnoses of plasmacytoma and metastatic carcinoma. FNAC revealed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most cases were primary and extraosseous lesions. However, both extraosseous and intraosseous lesions result in a variety of findings, including swelling associated or not with pain, facial asymmetry, numbness, paraesthesia, and hoarseness 17–98 . Notably, the findings indicated that most cases had a diagnosis of plasmacytoma (extramedullary or solitary of bone) and the remaining ones had systemic involvement by PCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation